The potential usage of palm oil mill effluent as animal feeder for poultries - Muhammad khair aiman, badrol hisham; Nur afiqah, adnan (2021)
Estimated around 90 million ton of lignocellulosic biomass, including empty fruit bunches (EFB) and oil palm trunks are produced by Malaysian Palm Oil Industry (POME). The worrying impact on social and ecology of palm oil on conservation of nation’s property as backwoods cover have been taken by the government to confine the palm oil plantation extension in 2010. The utilization of palm oil emanating for domesticated animals shown advantageous outcomes from palm oil effluent supplements. The crude or concentrated palm oil effluent emanating can be retained on cassava supper, dried grass or palm kernel cake and produced into dried feed cake. The POME components are assumed sustainable in deciding the utilization of POME as an animal feed source for poultry in Malaysia.